Drug- and/or trauma-induced hyperthermia? Characterization of HSP70 and myoglobin expression. - Benjamin Ondruschka; Franziska Rosinsky; Heiner Trauer; Eckhardt Schneider; Jan Dreßler; Heike Franke (PLoS ONE, 2018)
Heat shock protein 70 (HSP70) expression could be discussed as an adaption that promotes repair and counteracts cell damage. Myoglobin is released upon muscle damage of several pathways. The purpose of the present study was to determine whether the expression of HSP70 in kidney, heart and brain and of myoglobin in the kidney were associated with the cause of death and the survival times after lethal intoxications with three of the drugs most widely used in our local area (Saxony, Germany) as well as after fatal traumatic brain injury (TBI).We retrospectively collected kidney, heart and brain samples of 50 autopsy cases with toxicological proved lethal intoxication (main drugs methamphetamine, morphine, alcohol), 14 TBI cases and 15 fatalities with acute myocardial injury in age- and gender-matched compilations.Our main findings suggest that HSP70 is associated with hyperthermal and other stress factors of most cell populations. HSP70 expressions in kidney and heart muscle are useful for a differentiation between fatal intoxications and cases without toxicological influence (p < 0.05). There were significant differences in the cerebral expression patterns between methamphetamine- and morphine-associated deaths compared to alcohol fatalities (p < 0.05). An intensive staining of HSP70 in the pericontusional zone and the hippocampus after TBI (especially neuronal and vascular) was shown even after short survival times and may be useful as an additional marker in questions of vitality or wound age. A relevant myoglobin decoration of renal tubules was only shown for methamphetamine abuse in the study presented.In sum, the immunohistochemical characteristics presented can be supportive for determining final death circumstances and minimal trauma survival times but are not isolated usefully for the detection of drug- or trauma-induced hyperthermia.